DNA methylation affects freezing tolerance in winter rapeseed by mediating the expression of genes related to JA and CK pathways - Wei, Jiaping; Shen, Yingzi; Dong, Xiaoyun; Zhu, Yajing; Cui, Junmei; Li, Hui; Zheng, Guoqiang; Tian, Haiyan; Wang, Ying; Liu, Zigang (Frontiers in Genetics, 2022)
Winter rapeseed is the largest source of edible oil in China and is especially sensitive to low temperature, which causes tremendous agricultural yield reduction and economic losses. It is still unclear how DNA methylation regulates the formation of freezing tolerance in winter rapeseed under freezing stress. Therefore, in this study, the whole-genome DNA methylation map and transcriptome expression profiles of freezing-resistant cultivar NTS57 (NS) under freezing stress were obtained. The genome-wide methylation assay exhibited lower levels of methylation in gene-rich regions. DNA methylation was identified in three genomic sequence contexts including CG, CHG and CHH, of which CG contexts exhibited the highest methylation levels (66.8%), followed by CHG (28.6%) and CHH (9.5%). Higher levels of the methylation were found in upstream 2k and downstream 2k of gene regions, whereas lowest levels were in the gene body regions. In addition, 331, 437, and 1720 unique differentially methylated genes (DMGs) were identified in three genomic sequence contexts in 17NS under freezing stress compared to the control. Function enrichment analysis suggested that most of enriched DMGs were involved in plant hormones signal transduction, phenylpropanoid biosynthesis and protein processing pathways. Changes of genes expression in signal transduction pathways for cytokinin (CK) and jasmonic acid (JA) implied their involvement in freezing stress responses. Collectively, these results suggested a critical role of DNA methylation in their transcriptional regulation in winter rapeseed under freezing stress.